ANALISIS TINDAKAN OBSTRUCTION OF JUSTICE ADVOKAT DALAM TINDAK PIDANA KORUPSI - Harnita, Cici Merda; ', Erdianto; Rahmadan, Davit (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
Corruption in Indonesia is still facing many obstacles, one of the obstacles faced is the existence of measures to obstruct the process of enforcement of criminal acts of corruption committed by lawyers. Counted four advocates who have tripped obstruction of justice. This is a concern because advocates are respectable professions which are part of law enforcement. As for the writing of these goals, namely; First, law enforcement efforts against obstruction of justice advocates in corruption cases in Indonesia, secondly, the link between law enforcement against lawyers accused of carrying out obstruction of justice with advocate's immunity rights.This type of research can be classified in the type of normative research, because the authors only do research by examining library materials or secondary. Normative research is reviewed by the author regarding an inventory of positive law, and legal principles. Data sources used are primary legal materials, secondary legal materials and tertiary legal materials, data collection techniques in this study with library study methods or documentary studies.From the results of the research problem there are two main things that can be concluded. First, law enforcement actions of obstruction of justice advocate in corruption crimes in Indonesia, that law enforcement here has not been effective because related legal norms have not been adhered to by all legal subjects, this is influenced by three components of law enforcement namely the substance of law, law enforcement and legal culture. Secondly, the link between law enforcement and lawyers accused of carrying out obstruction of justice with advocate's immunity rights is related to the fact that the position of advocate is susceptible to intersecting with obstruction of justice if the advocate defines the immunity rights that he has without considering the limitations set out in the law and advocate's code of ethics. The author's suggestion, first, the legislators are expected, in drafting the law or renewing the law to improve its performance by making authentic interpretations in every article formulation, second, it is expected for law enforcement officers, in eradicating corruption must be serious indeed, not looking at a legal norm is more important than other legal norms; build mutual understanding between law enforcers and improve the professionalism of law enforcement as well as accuracy, independence and not selective, correcting law enforcement institutions.Keywords : Obstruction of justice – Advocate – Criminal Act – Corruption